Mining Evidences of Internet of Robotic Things (IoRT) Software from Open Source Projects - Albonico, Michel; Rohling, Adair; Santos, Juliano; Varela, Paulo (Anais do Simpósio Brasileiro de Componentes, Arquiteturas e Reutilização de Software (SBCARS); 2021: Anais do XV Simpósio Brasileiro de Componentes, Arquiteturas e Reutilização de Software, 2021)
The current world scenario is heading to contactless technologies, where robots are in the center. These systems usually benefit from Internet of Things (IoT) sensing, being named Internet of Robotics Things (IoRT) systems. Developing IoRT software naturally involves high levels of complexity, which may be softened with well-established architectural evidence. In this paper, we aim at mining IoRT software architectural evidence from open source IoRT software repositories. For this, we (i) extract a dataset from GitHub repositories containing real open-source IoRT systems, (ii) mine relevant information from those repositories, (iii) and compile a catalog of architectural software characteristics. The catalog from our study can then be used by practitioners architects.